المنهج المعرفي التوحيدي عند عبد الوهاب المسيري: مدخل إلى الإبستمولوجيا التوحيدية - الحاج بن أحمنه دواق (International Institute of Islamic Thought, 2012)
سعى البحث إلى تحليل جهود عبد الوهاب المسيري في ملاحظة فشل المناهج المادية التي تبناها الغرب في صياغة المعرفة ونقدها، وتوظيفها في صياغة الواقع الإنساني. وقد تبين للمسيري أن سبب هذا الفشل هو بُعد المناهج المادية عن القيم المطلقة الموجهة بأحكام الوحي وأخلاقه، ما جعله يطرح بديلاً على مستوى الرؤية والمنهج، يقوم على النموذج المعرفي التوحيدي، الذي يبحث في أصول الظواهر ومآلاتها، ويقرأ فيها الإلهي المتجاوز. This study has analyzed efforts of Abdelwahab El-Messiri in his observation of the failure of Western materialism in formulating and testing knowledge, and the shaping of human life. El-messiri has found that this failure is due to material approach which is devoid of values guided by revelation and its ethics. El-Messiri has suggested the Tawhidi epistemology as an alternative. This alternative epistemology would study the origins of the phenomena under study, and its ends, and conclude with presence of the divine.